2014
DOI: 10.1371/journal.pone.0103976
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+ Sensor Protein Swiprosin-1/EFhd2 Is Present in Neurites and Involved in Kinesin-Mediated Transport in Neurons

Abstract: Swiprosin-1/EFhd2 (EFhd2) is a cytoskeletal Ca2+ sensor protein strongly expressed in the brain. It has been shown to interact with mutant tau, which can promote neurodegeneration, but nothing is known about the physiological function of EFhd2 in the nervous system. To elucidate this question, we analyzed EFhd2−/−/lacZ reporter mice and showed that lacZ was strongly expressed in the cortex, the dentate gyrus, the CA1 and CA2 regions of the hippocampus, the thalamus, and the olfactory bulb. Immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 44 publications
6
64
0
Order By: Relevance
“…Previous studies [17, 20, 21] showed that swiprosin-1 was widely accumulated in tissues such as the spleen, lung, liver, heart, and brain in particular. Swiprosin-1 was also expressed in immune cells such as human and primary murine mast cells [14], murine B cells, T cells [15-17], macrophages, natural killer cells [18, 19], and human peripheral blood mononuclear cells [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies [17, 20, 21] showed that swiprosin-1 was widely accumulated in tissues such as the spleen, lung, liver, heart, and brain in particular. Swiprosin-1 was also expressed in immune cells such as human and primary murine mast cells [14], murine B cells, T cells [15-17], macrophages, natural killer cells [18, 19], and human peripheral blood mononuclear cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Swiprosin-1 was also expressed in immune cells such as human and primary murine mast cells [14], murine B cells, T cells [15-17], macrophages, natural killer cells [18, 19], and human peripheral blood mononuclear cells [20]. Protein atlas database indicates that swiprosin-1 is moderately expressed in human renal glomeruli but not tubules (http://www.proteinatlas.org/ENSG00000142634-$EFHD2/tissue/kidney#imid_13574299), which is consistent with the finidng of the present study that swiprosin-1 was moderately expressed in podocytes of renal glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in murine neurites, co‐localization of swiprosin‐1 with tau, MAP2, synapsin 1a/b, and PSD‐95 signifying that swiprosin‐1 could be also associated with transport vesicles delivering synaptic proteins and it serve as a synaptic protein. For example, swiprosin‐1 ‐/‐ mice increases the speed of axonal transport but its presence inhibited the KIF5A (kinesin) mediated MT (microtubules) gliding in a dose‐dependent manner [Purohit et al, ]. Similarly, Borger et al also showed knockdown of swiprosin‐1 facilitates the development of a larger number of synapses in neurons but did not affect their ability to convert to mature synapses by recruiting postsynaptic densities [Borger et al, ].…”
Section: Swiprosin‐1 In Neuron Axonal Transportmentioning
confidence: 99%